(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article provides information about social conflicts and conflicts as a source of moral and spiritual disorders. Also, opinions were expressed about the history of human development, various conflicts, conflicts, and contradictions between individuals, people, groups, different communities, peoples, nations, peoples, and states at each of its stages.